Weather-rice-nutrient integrated decision support system (WeRise) - CGIAR Research Program on Rice (2018)
This technology was developed through on-station and on-farm experiments in Central Java, Indonesia and a multi-location field validation was conducted in North Sumatra and West Nusa Tenggara provinces for evaluating prediction skill in collaboration with local partners in research and agricultural extension.